2011
DOI: 10.1093/jac/dkr179
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic usage in south-western French hospitals: trends and association with antibiotic stewardship measures

Abstract: This first longitudinal study, in 74 hospitals, showed that human resources and persuasive ABS measures, in the context of a multidisciplinary approach, are helpful in controlling total antibiotic and fluoroquinolone use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…The situation in the UK contrasts with recent data from the United States, with just over half of hospitals ( n = 206 of 406 responding hospitals) reporting the existence of an AMT . Similarly, just over half of hospitals reported an AMT in south‐western French hospitals (56% of 74 responding hospitals) . In our study, the presence of an AMT was significantly associated with presence of infectious disease, microbiology and emergency departments.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The situation in the UK contrasts with recent data from the United States, with just over half of hospitals ( n = 206 of 406 responding hospitals) reporting the existence of an AMT . Similarly, just over half of hospitals reported an AMT in south‐western French hospitals (56% of 74 responding hospitals) . In our study, the presence of an AMT was significantly associated with presence of infectious disease, microbiology and emergency departments.…”
Section: Discussioncontrasting
confidence: 99%
“…16 Similarly, just over half of hospitals reported an AMT in south-western French hospitals (56% of 74 responding hospitals). 17 In our study, the presence of an AMT was significantly associated with presence of infectious disease, microbiology and emergency departments. Furthermore, hospitals in England and those with higher bed capacity were also more likely to have an AMT.…”
Section: Discussionsupporting
confidence: 47%
“…37 Eighty-five perecent of these hospitals had antibiotic advisors. On the other hand, Dumartin's group [37][38][39] reported that pharmacist time dedicated to antibiotic management, restrictive dispensation using stop-orders, computerized tools, continuing education, and audits were components that remained underused. Components identified as playing a role in AS were similar to those reported in the HAIG survey and the extent to which these structure and processes have been implemented within the VA was comparable with that in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Components identified as playing a role in AS were similar to those reported in the HAIG survey and the extent to which these structure and processes have been implemented within the VA was comparable with that in other studies. [37][38][39] However, each of these studies addressed only a few components and none is as comprehensive as the HAIG survey in examining ASP components.…”
Section: Discussionmentioning
confidence: 99%
“…142,143 Guidelines for treatment of infections should be reviewed to ensure that alternatives to broad-spectrum agents are provided and that de-escalation of antibiotics and reductions in use of specific antimicrobial classes and total antibiotic burden are emphasized. 139,144 Antimicrobials such as carbapenems, fluoroquinolones, and metronidazole have been identified as possible risk factors for acquisition of CRE. 3,6,92,101 In the setting of CRE transmission, whether sporadic or epidemic, it is important to ensure minimization of unnecessary and unnecessarily broad-spectrum antibiotic use.…”
Section: Local and National Antimicrobial Stewardship (Ams) Programsmentioning
confidence: 99%